Pengembangan Media Pembelajaran Modeling melalui Video dalam Peningkatan Kemampuan Toilet Training pada Anak Tunagrahita - Ima Sukmawati; Elis Noviati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to improve the ability of toilet training in mentally retarded children through video modeling. The research method used a pre-experimental design with a one-group pre-test and post-test design. The results showed the effect of video media modeling on the toilet training ability of mentally retarded children, with an average increase of 1.59. The Wilcoxon test shows a p-value of 0.001. In conclusion, video media modeling has an effect on the toilet training ability of mentally retarded children. Keywords: Children with Mental Retardation, Video Media Modeling, Toilet Training